The Effect of KOURIBGA (Family Planning Postpartum Bouquet Ribbon Game) Education on The Self-Efficacy of Health Cadres - Ramadhani Anggi Wahyu Nurjanah; Niken Bayu Argaheni; Nurul Jannatul Wahidah; Revi Gama Hatta Revi Gama Hatta Novika; Siti Nurhidayati (PT. Anagata Sembagi Education, 2024)
The low self-efficacy of health cadres can impact the effectiveness of community education on postpartum family planning (KBPP). Previous studies indicate that with appropriate educational methods, the number of KBPP users can increase significantly. The Simulation Game known as the Family Planning Postpartum Bouquet Ribbon Game, or KOURIBGA, presents a promising approach to health education by offering an engaging and interactive simulation format. This study aimed to analyze the influence of KOURIBGA education on the self-efficacy of health cadres in Kedungwinong Village, Nguter District, Sukoharjo Regency. Employing a pre-experimental, pretest-posttest design, the research used a total sample of 35 health cadres. In this study, the KOURIBGA education served as the independent variable, while the dependent variable was the self-efficacy of the cadres. The results, analyzed using the Wilcoxon test, indicated a significant effect (p-value < 0.05), demonstrating that KOURIBGA education positively influenced health cadres' self-efficacy in Kedung Winong Village. Thus, KOURIBGA education can be effectively utilized to enhance self-efficacy, contributing to better reproductive health services.